China and North Africa Since World War II a bilateral approach - Olimat, Muhamad (Lexington Books, 2014)
This manuscript examines Sino-North Africa relations on a bilateral level since World War II. It highlights the depth of Chinau2019s involvement in the region with each country on a five dimensional approach: energy security, trade relations, political relations, arms sales/security cooperation, and cultural relations. Regarding each of these criteria, North Africa holds a strategic significance to China